Onde estão os ricos? - Confins (Confins)
To answer the question "where are the rich?" FGV Social researchers used data from the Federal Revenue on the Personal Income Tax (IRPF) declarations of 2018. The text maps the results by municipality and shows its concentration in the Southeast, South and - increasingly - in the Centro-Oeste, in Brasília and in the soy, corn and cotton production region.